The rancher's holiday arrangement [large type] - Minton, Brenda (Minton, Brenda. Mercy Ranch., 2020)
"Rancher Joe Lawson prefers his own company--until he rescues Daisy West and her twin foster babies from a car accident. When Daisy returns the favor by announcing their fake engagement to save him from his meddling family, Joe's quiet life turns upside down. Now he's engaged to his boss's daughter ... and if he's not careful, this cowboy might just fall hat over heels for her."--Amazon.com.